2007
DOI: 10.1098/rspb.2007.0353
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the risk from ovine BSE and the impact of control strategies

Abstract: Although no naturally infected sheep with bovine spongiform encephalopathy (BSE) has ever been discovered, it remains possible that BSE once infected the UK sheep population, has been transmitted between sheep, and is still present today. We constructed a mathematical model to assess the current maximum theoretical exposure to consumers from BSE-infected ovine material and to estimate the risk reduction that could be achieved by abattoir-based control options if BSE-infected sheep were ever found in the nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The occurrence of atypical cases in the sheep population under selection justifies continued monitoring for scrapie prevalence. Since BSE can infect sheep, this monitoring is also essential for understanding the theoretical risk of BSE in the sheep population [16,21]. …”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of atypical cases in the sheep population under selection justifies continued monitoring for scrapie prevalence. Since BSE can infect sheep, this monitoring is also essential for understanding the theoretical risk of BSE in the sheep population [16,21]. …”
Section: Discussionmentioning
confidence: 99%
“…To date, surveillance using biochemical tests that can discriminate between experimental ovine BSE and scrapie has failed to detect any evidence of naturally BSE-infected sheep (Thuring et al, 2004;Eloit et al, 2005;Sharpe et al, 2005;Stack et al, 2006), although there have been one confirmed case (Eloit et al, 2005) and one suspected case of natural BSE in goats. The risk to the human population of BSE in sheep requires further investigation and key to estimating such a risk is the calculation of the prevalence of BSE in sheep at any given point in time, which is in turn dependent on the susceptibility of sheep to the BSE agent and the efficiency of subsequent sheep-to-sheep and sheepto-human passage (Baylis, 2002;Ferguson et al, 2002;Kao et al, 2002;Fryer et al, 2007). Inaccurate data on BSEsusceptible ovine genotypes could potentially have a significant effect on the assessment of risk of BSE in sheep to the human consumer (Kao et al, 2003).…”
mentioning
confidence: 99%
“…A full description of the model variables, parameters and equations is presented in Fryer et al 2007 [23], reproduced in Boden et al 2010 [16].…”
Section: Methodsmentioning
confidence: 99%